Estado da arte sobre ensino desenvolvimental com Jovens e Adultos no catálogo de teses e dissertações da CAPES - Souza, Regina Vieira de. (Universidade Federal do Tocantins, 2022)
This research results from an investigation developed in the Scientific Initiation Program (PIBIC), as a scholarship student at the Federal University of Tocantins (UFT), during the years 2019 to 2021, on the theme of developmental teaching and Youth and Adult Education